Selection Participants Of Science Olympic In Elementary School Using Fuzzy – Profile Matching Method - I Komang Wiratama; Tuti Marjan Fuadi; Emy Yunita Rahma Pratiwi; Deddy Kurniawan; I Gede Iwan Sudipa (Institute of Computer Science (IOCS), 2022)
Science ability is one of the students' potentials that can be developed and can be competed. Every student's potential in the field of science can be excelled and directed to become ability. Science Olympiad is a forum to show students' abilities so that every elementary school is expected to participate. Schools must, of course, determine prospective participants for the science olympiad, with the selection of potential students with predetermined assessment criteria. In this study, implementing decision support with fuzzy logic for the conversion of criteria values ??and the Profile Matching method in determining the ideal profile of prospective Olympic participants, each student's alternative value on the criteria is obtained by the difference in value with the ideal profile, the smaller the value of the GAP difference, it indicates the best alternative. The results showed that the results of fuzzy and profile decisions were the three best alternatives for students who participated in the science Olympics.